Lois C. answered • 06/09/20

Knowledgeable, experienced tutor specializing in secondary mathematics

If you set this up using quadratic formula where "a" = 9, "b" = 24, and "c" = 19, you will have the following:

x = [ -24 ± √ 24^{2} - 4(9)(19) ]/ 18. Simplifying within the radical and rewriting the negative radicand in terms of ** i**, you will have x = [ -24 ± 6

**√3 ]/18, and this, once you separate the real and the imaginary parts and reduce the fractions, will simplify to x = -4/3 ±**

*i***√3/3.**

*i*